Przybliżone Metody Badania Ruchu Konturu Roponośnego Przy Filtracji Cieczy Ściśliwej w Złożu - Walden, H. (Engineering Transactions, 1961)
In this paper approximate (methods are proposed for the investigation of the motion of an oil front in the process of flooding, the arrangement and injection wells being arbitrary. of producing in the case of the flow of a compressible liquid, the problem reduces to that of solving heat conductivity equation, with the application of the superposition method for positive and negative sources. For time-variable flows in each particular well the solution (4.14) is obtained enabling the determination of the displacement of any point on the oil front and, in consequence, the motion of the entire front after the time Δt. Assuming the flow rates to be invariable in time, this solution reduces to a more simplified form, (4.18) and (4.19). To appraise the results obtained, a numerical computation example is given. It is shown that the methods described may find practical application to the computation and correct control of the motion of the front at each stage of the exploitation of the oil deposit.